Hubungan Pola Asuh Ibu dengan Tingkat Kemandirian Anak Secara Fisik Usia (4-6) Pra Sekolah di Raudhatul Atfal Al-Falah - Nila Khusnatun Nihayah; Kurnia Wijayanti; Nopi Nur Khasanah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to determine the relationship between maternal parenting styles and the level of physical independence of preschool children (aged 4–6 years) at Raudhatul Athfal Al-Falah Sampang Karang Tengah Demak. Children's independence is an important aspect of growth and development, especially the ability to perform daily physical activities without dependence on others. This study used an analytical quantitative method with a cross-sectional approach. The sample consisted of 70 respondents selected using total sampling technique according to the inclusion criteria. Data were collected using a questionnaire that had been tested for reliability, then analyzed univariately and bivariately using Spearman's rank correlation test. The results showed that most mothers applied a democratic parenting style (51.4%), followed by permissive (41.4%) and authoritarian (7.1%). The level of children's physical independence was mostly in the independent category (55.7%). Bivariate tests showed a significant relationship between maternal parenting styles and children's physical independence (p = 0.002; r = –0.363). Parenting styles play a role in shaping children's physical independence, so a balanced parenting style between discipline and support is needed for children to develop optimally.